ANALISIS BENTUK, FUNGSI, DAN AKUISISI BAHASA TABU PADA SISWA TINGKAT DASAR: KAJIAN PRAGMATIK DAN SOSIOLINGUISTIK - Masrur, Irfan; Maghfirah, Naily Inayatul (International Conference on Humanity Education and Society (ICHES), 2024)
Taboo language is a number of words that are avoided from being used or pronounced because they are very sensitive for certain groups. In fact, if these taboo words are spoken, they can cause anger in the person they are talking to. Based on the result of observation, elementary level students at MI Shibyanul Islamiyah occasionally use taboo language when interacting with their friends. This research aims to analyze the form of taboo language used, how taboo language is used, and how taboo language is acquired among elementary level students. The approach used is a case study, with data collection techniques in the form of observation, interviews and documentation. From the results of data collection, it is known that the forms of taboo language used by students at MI Shibyanul Islamiyah are the names of certain animals, jargon or special terms, dirt, supernatural creatures, and certain disorders/deficiencies. Apart from that, it was found that taboo language was used to joke, curse, and show anger towards the interlocutor. Meanwhile, the acquisition of taboo language at MI Shibyanul Islamiyah is unconscious through the school environment, outside of school, and the videos they watch on their cell phones at home.